Human resources : business English - Helm, Sara; Utteridge, Rebecca (Harlow, England Pearson, 2010)
This new range of specialist titles extends the scope of the Market Leader series and allows teachers to focus on specific areas of business such as law, banking and finance, logistics and human resources. These titles can be used on their own or alongside other business English coursebooks
Keywords: Inglés (Lengua) -- Estudio y enseñanza